Prispevek k poznavanju favnistike in ekologije pajkov severovzhodne Slovenije (Arachnida: Araneae) - Kuntner, Matjaž (Natura Sloveniae, 1999)
A list of 102 spider species collected between 24 and 31 July 1997 at 16 localities of north-eastern (subpannonian) Slovenia is given. One family, three genera and thirteen species are new to the fauna of Slovenia. A preliminary result of an investigation into spider species richness, the thirdin a series of such experiments in Slovenian forests, indicates that the surveyed forest near the village Obrež is moderately rich in species (72-86 species).
Keywords: Arachnida; Classification; Ecosystem; favna; pajki; Slovenia; Slovenija; Spiders